2007
DOI: 10.1673/031.007.2701
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Dynamics of Behavioral Thermoregulation by Adults of the GrasshopperMelanoplus sanguinipes

Abstract: The short-term behavioral responses of adult grasshoppers, Melanoplus sanguinipes (F.) (Orthoptera: Acrididae), were examined after they experienced changes in microclimate when beingforced to change positions in their habitat. It was also determined if and when behavioral tactics allowed adults to achieve body temperatures within their preferred range. The preferred or set-point range, here taken as the interquartile range of temperatures selected on a laboratory thermal gradient, was estimated to be 37.4–40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In fact, in the case of endotherms for which the ecogeographic rules were originally formulated, a number of discrepancies occur and it is not always possible to explain the geographic body size trends by simple thermoregulatory models. This situation becomes more complex when trying to verify the rules in ectotherms that, in most cases, regulate body temperature behaviourally, as is the case of most studied Orthoptera [31][32][33][34][35].…”
mentioning
confidence: 99%
“…In fact, in the case of endotherms for which the ecogeographic rules were originally formulated, a number of discrepancies occur and it is not always possible to explain the geographic body size trends by simple thermoregulatory models. This situation becomes more complex when trying to verify the rules in ectotherms that, in most cases, regulate body temperature behaviourally, as is the case of most studied Orthoptera [31][32][33][34][35].…”
mentioning
confidence: 99%
“…Although the behaviours we observed during the laboratory experiments (stilting, shade seeking, movement into the vertical position) are generally accepted as being common thermoregulatory behaviours in other grasshoppers (Anderson et al, 1979;Chappell, 1983;O'Neill and Rolston, 2007;Whitman, 1987), measurements of the resulting temperature changes are rare.…”
Section: Thermal Consequences Of Behaviours In the Laboratorymentioning
confidence: 93%
“…Gillis and Smeigh, 1987;Willott, 1997) relating them to the operative temperature of non-thermoregulating models (Hertz et al, 1993). Field studies on grasshoppers have demonstrated that the proportion of individuals exhibiting behaviours such as basking, stilting or crouching is related to surface temperatures (Chappell, 1983;Gilman et al, 2008;O'Neill and Rolston, 2007;Samietz et al, 2005), but few studies have attempted to measure the change in body temperature accompanying particular behaviours. Basking has been shown to lead to increases in body temperature under exposure to solar radiation, but the effects of passive warming and active thermoregulation are not always distinguished (Carruthers et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Fire ants are able to raise their nest temperature by modifying their nest shape relative to the sun's angle, while wood ants use solar radiation in combination with behavioral modifications to maintain ideal nest temperatures (Vogt et al, 2008;Galle, 1973). Non-communal insects such as grasshoppers bask to increase their T B (O'Neill & Rolston, 2007). Butterflies in general often bask or use ground contact to gain heat by conduction and convection then seek shade or minimize their exposed wing surface area to either facilitate heat loss or decrease heat absorption (Clench, 1966).…”
Section: Invertebratesmentioning
confidence: 99%